Hamiltonian Paths in Some Classes of Grid Graphs - Fatemeh Keshavarz-Kohjerdi; Alireza Bagheri (Journal of Applied Mathematics)
The Hamiltonian path problem for general grid graphs is known to be NP-complete. In this paper, we give necessary and sufficient conditions for the existence of Hamiltonian paths in L-alphabet, C-alphabet, F-alphabet, and E-alphabet grid graphs. We also present linear-time algorithms for finding Hamiltonian paths in these graphs.